«УЛЛЫ ЖЫРАЎДЫӉ СЫРЛЫ ҚУБЫЛЫСЛАРЫ» (Қаражан улы Нурабулла жыраў ҳаққында) - Аяпов, С. (SCIENCE and SOCIETY, 2024)
This article is written about Nurabulla Zhirov, the son of Karazhan, who occupies a significant place in the work of the Karakalpak Zhirov, the teacher of several famous students. In addition to the legends about Zhirov in the mouths of the people, we also mentioned the information that his descendants told us about Zhirov.